Optimising Neurodevelopment in Preterm Low Birth Weight Infants through Structured Early Physiotherapy - N. Meena (An Overview of Disease and Health Research Vol. 1, 2025)
Background: Preterm birth and medical complications related to Low birth weight can adversely affect long-term development, often leading to neuromotor delays, intellectual disabilities, and behavioural challenges. Early Intervention involves delivering specialised therapeutic programs to infants at risk of developmental delays with regular evaluations of their motor skills, cognitive abilities, language development, and adaptive functioning. Aim: This study investigated the effect of early physiotherapy intervention on the neurodevelopmental outcomes of preterm low birth weight (LBW) infants during their first six months of life. Methodology: A total of 100 preterm LBW infants were admitted to the Neonatal Intensive Care Unit (NICU) and the Referral Newborn (RNB) Unit at Raja Muthiah Medical College and Hospital (RMMC&H) and recruited for the study. The Early Intervention (EI) group consisted of infants who consistently received early physiotherapy sessions. In contrast, the Non-Early Intervention (NEI) group included infants whose families declined participation despite being advised and counselled. The Amiel-Tison Neurologic Examination assessed neurological function. At the same time, the Denver Developmental Screening Test (DDST) evaluated developmental milestones, covering the gross motor, fine motor/adaptive, language, and personal-social domains. The therapist conducted assessments at six months of corrected age. Results: The results revealed that infants in the EI group exhibited significantly better outcomes across all assessed domains than those in the NEI group. Improvements were particularly notable in gross motor and language development. These findings highlight the critical role of early physiotherapy in enhancing neurodevelopmental trajectories among high-risk preterm LBW infants. Conclusion: Early therapeutic engagement during the neonatal period is essential for promoting more favourable long-term developmental outcomes and mitigating the risk of delays. This study supports integrating structured early physiotherapy programs into routine neonatal care practices to improve the quality of life and developmental potential of this vulnerable infant population.